Implications of the anti-aging efficacy of BaZi Bu Shen capsules for human longevity and development - Meng, Zuohuan; Ma, Wenyuan; Zhao, Xinke (Frontiers in Aging, 2025)
At present, there are no approved drugs for the treatment of aging, but a number of studies have reported related anti-aging drugs. As an innovative traditional Chinese medicine (TCM) that has been on the market for many years to treat waist and knees soreness, dizziness, tinnitus, fatigue, and cold limbs caused by insufficient kidney-yang, “Bazi Bushen Capsules (BZBS)” has also made a series of new and remarkable achievements in anti-aging research, which is expected to become the first new drug approved by the National Medical Products Administration (NMPA) for anti-aging indications, thus opening up new ideas for the medical field to treat aging. In the context of anti-aging, the general social phenomenon expected to be effectively caused is that people will enter a new era of longevity, and most countries will move from the current aging society to the aged society and even into the super-aging society in the near future. This remark provides forward-looking and guiding suggestions for future research on the relationship between longevity, economy and social protection.